2021
DOI: 10.1007/s40195-021-01264-8
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviors of Nitride Coatings on Titanium Alloy in NaCl-Induced Hot Corrosion

Abstract: TiN and TiAlN coatings were deposited by arc ion plating on titanium alloys to study their hot corrosion resistance when they were exposed to NaCl at 600 °C. The microstructure and corrosion behaviors of nitride coatings were studied using scanning electron microscope, X-ray diffraction, electro-probe microanalyzer and X-ray photoelectron spectroscopy. The results showed that nitride coatings with the different compositions and the ones with the same composition but different thicknesses presented different ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Furthermore, as human activities are increasingly expanding to coastal areas, the hot-end components in these regions face a more serious corrosive environment. The presence of NaCl particles in humid air can easily deposit on the surface of these components, accelerating the process of hot corrosion [4][5][6]. In order to mitigate or prevent hot corrosion, the preparation of protective coatings on the surface of materials is a highly economical and universally applicable method [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as human activities are increasingly expanding to coastal areas, the hot-end components in these regions face a more serious corrosive environment. The presence of NaCl particles in humid air can easily deposit on the surface of these components, accelerating the process of hot corrosion [4][5][6]. In order to mitigate or prevent hot corrosion, the preparation of protective coatings on the surface of materials is a highly economical and universally applicable method [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research, the application of protective surface coatings is a preferred way to enhance corrosion resistance [20]. Naveen Kumar et al [21] found that 86WC-10Co-4Cr-coated AISI316 stainless steel exhibited a much lower weight increase (1.1880 mg/cm 2 ) than untreated specimens (2.6857 mg/cm 2 ) in 88Fe 2 (SO 4 ) 3 -12%Na 2 SO 4 corrosive environment for 50 cycles at 650 • C. Du et al [22] prepared TiSiCN/Ag nanocomposite coatings on titanium alloy substrates and found that the mass gain in the titanium substrate was 2.750 mg/cm 2 , while the mass gain in the coating was 1.937 mg/cm 2 after 2 of 17 hot etching at 550 • C for 72 h. These coatings provide additional protection by preventing contaminated salt from attacking the substrate [21][22][23][24][25][26][27][28]. One promising coating technique for improving the hot corrosion resistance of titanium alloys is the preparation of aluminate coatings [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the protection was related to the SiO 2 layer formed during a hot corrosion test. TiN and TiAlN coatings were deposited using arc ion plating on titanium alloys to study their hot corrosion resistance when they were exposed to NaCl at 600 • C [42]. A 12 µm thick TiN coating showed poor corrosion resistance due to its porous and nonprotective oxide scale, whereas for a TiAlN coating produced in a corrosive environment, an Al 2 O 3 scale acted as a barrier retarding the inward transport of corrosive species.…”
Section: Introductionmentioning
confidence: 99%